Development Model for OBE-Interated Software Development Micro-Specializations in Medicine-Engineering Interdisciplinary Context - Chang, Yonghu; Liu, Lianghui; Li, BingMing; Zhou, Qing (Journal of Educational Research and Policies, 2026)
In the context of Emerging Engineering and New Medicine education initiatives, the demand for interdisciplinary and innovative professionals in medicine-engineering convergence fields is escalating. Traditional pedagogical paradigms inadequately address the advanced software development competency requirements of emerging specialties such as intelligent medical engineering. This paper proposes an OBE (Outcome-Based Education)-driven framework for constructing a software development micro-specialization cluster tailored to medicine-engineering interdisciplinary programs. Through backward-designed curriculum systems, integrated project-driven pedagogy, enhanced practical training, and diversified assessment mechanisms, this model elevates students’ software development capabilities and engineering practice literacy. The proposed approach effectively bridges the gap between conventional curricula and industry demands, offering a viable pathway for software design courses within the medicine-engineering interdisciplinary landscape.